Opportunities for the Transformation and Development of Power Plants Under Water Stress Conditions: Example of Adamów Power Plant - Tomasz Kałuża; Jolanta Kanclerz; Mateusz Hämmerling; Ewelina Janicka-Kubiak; Stanisław Zaborowski (Energies)
In the vicinity of the Adamów power plant, which operates in the catchment area of the Kiełbaska river, there is a significant shortage of water resources caused by the intensive use of water by the energy industry and agriculture. The development of the plant by replacing the outdated coal-fired (lignite-fired) units with modern gas and steam units may contribute significantly to reducing the negative impact on the environment and reduce the demand for water resources relative to coal technology. Gas and steam units are a much more energy-efficient technology. This implies a lower demand for water, a reduction in pollutant emissions, and greater operational flexibility, which enables the units to adapt to changing hydrological and environmental conditions. The high efficiency of these units limits the need for frequent water-refilling, while allowing for a more sustainable and stable production of energy. Based on an analysis of hydrological data for the years 2019–2023, it was estimated that water stress is observed in this catchment area on 198 days per year, which accounts for c.a. 54% of the hydrological year. Therefore, it is assumed that inter-catchment pumping stations with a flow of 0.347 m3∙s−1 will be required. This sets the demand for water at 5.95 million m3 per year. The planned water transfer will be carried out from Jeziorsko reservoir on the Warta river through the catchment area of Teleszyna river. Moreover, there are plans for the reconstruction of the layout of Kiełbaska Duża and Teleszyna rivers, which would involve the restoration of natural run-offs, following the discontinuation of open-pit lignite mining. This will additionally be supported by the reduced demand for water in the water use system when using the modernised power plant. The analysed data made it possible to develop hydrological scenarios that take the future reduction in water stress into account by implementing plans to restore the former hydrographic system in the region. These investments would also foresee the creation of new retention reservoirs (in former mining pits) with a capacity of nearly 900 million m3, which will significantly increase the region’s water resources and retention potential, supporting hydrological and energy security for the years to come.